The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/mar.21626
|View full text |Cite
|
Sign up to set email alerts
|

What makes products look premium? The impact of product convenience on premiumness perception

Abstract: This study examines the impact of product convenience on premiumness perception. A comparative survey and four experiments confirm that products viewed as convenient are perceived as more premium than their less convenient counterparts. This effect persists even when the overall quality and preference of the convenient product is equivalent to a less convenient counterpart. The convenience–premiumness relationship is driven by perceptions of convenient products' manufacturers being more customer‐oriented. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…The researcher found a positive relationship between the website convenience and the intention to buy the products online. Another previous study has confirmed the positive and significant relationship between the website convenience and intention to purchase online through different websites (Cho et al, 2022). After analyzing the previous studies, the following hypothesis was developed: H1: Website convenience has a significant and positive influence on the consumer intention to purchase online in Malaysia…”
Section: Online Purchase Intention and Website Conveniencementioning
confidence: 92%
“…The researcher found a positive relationship between the website convenience and the intention to buy the products online. Another previous study has confirmed the positive and significant relationship between the website convenience and intention to purchase online through different websites (Cho et al, 2022). After analyzing the previous studies, the following hypothesis was developed: H1: Website convenience has a significant and positive influence on the consumer intention to purchase online in Malaysia…”
Section: Online Purchase Intention and Website Conveniencementioning
confidence: 92%